2015
DOI: 10.12740/pp/38439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of chosen factors in predicting post-stroke depression: a one year follow-up.

Abstract: We found the association between the presence of PSD and location of lesions (frontal lobes or basal ganglia), as well as with the degree of functional improvement during 12 months after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Our study has the following strengths. A large amount of publications on PSD were identified, resulting in a rich pooled cohort of studies that were not included in earlier meta-analyses (Chen et al 2013 , 2016 ; Gozzi et al 2014 ; Jiang et al 2014 ; Metoki et al 2016 ; Saxena and Suman 2015 ; Terroni et al 2015 ; Wei et al 2016 ; Wichowicz et al 2015 ; Zhang et al 2016 ). Furthermore, beside information on lesion laterality, also data on other imaging markers was retrieved for quantitative and qualitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has the following strengths. A large amount of publications on PSD were identified, resulting in a rich pooled cohort of studies that were not included in earlier meta-analyses (Chen et al 2013 , 2016 ; Gozzi et al 2014 ; Jiang et al 2014 ; Metoki et al 2016 ; Saxena and Suman 2015 ; Terroni et al 2015 ; Wei et al 2016 ; Wichowicz et al 2015 ; Zhang et al 2016 ). Furthermore, beside information on lesion laterality, also data on other imaging markers was retrieved for quantitative and qualitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the location of lesion was related to PSD (42)(43)(44), such as prefrontal, temporal lobe, etc. However, in this study the association between the lesion location and the onset of depression was not found, may be caused by including patients with lesion volume varied from lacunar infarction to large cerebral infarction, and there was a correlation between lesion volume and severity of depression (45,46).…”
Section: Discussionmentioning
confidence: 98%
“…Only a few studies reported male gender as an independent predictor for PSD (28). Some studies showed no association with gender [ 21 ]. PSD is consistently linked with low social support levels.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors like age, gender, psychiatric illness, family history of psychiatric illness, hypertension, diabetes mellitus (DM), angina pectoris, current cigarette smokers, low socioeconomic status, low monthly income, unemployment, marital status, and educational background as well as the involvement of the left hemisphere of the brain of the patient are associated with PSD [ 2 5 , 7 , 12 21 ]. Most of these prestroke and poststroke risk factors reduce the potential to cope with disability and are more relevant predictors of PSD in developing countries of SSA.…”
Section: Introductionmentioning
confidence: 99%